Experimental investigation of the effects of preheating temperature on low-temperature cold start performance, emissions and energy conversion of diesel-electric hybrid. (1st April 2023) - Wang, Peng; Qin, Biao; Shi, Lei; Kang, Wei; Zhao, Bin; Deng, Kangyao
Highlights: A method for preheating intake air, coolant, and lubrication to solve the difficulty of cold start at low temperatures of diesel-electric hybrids was proposed. The intake air preheating consumed less energy and maintained a high energy conversion efficiency, whereas coolant and lubrication preheating consumed more energy, and the energy conversion coefficient decreased significantly with an increase in the preheating temperature. The inflection point of the energy conversion efficiency curve was found. The phenomenon of ineffective intake preheating was found and its boundary point was obtained, which depends mainly on the starting resistance torque and starting torque. With the increase in intake temperature, the ignition delay period was shortened. This led to an earlier SOC and 50% combustion position point, resulting in an increase in the IMEP and enhanced combustion stability. At 233 K ambient temperature, the minimum electrical energy consumption for the combined coolant with intake air preheating was 2557 kJ with a successful start. In contrast, the minimum electrical energy consumption for the combined lubricant with intake air was only 379 kJ. However, the emission performance of coolant preheating was better than that of lubrication preheating. The starting time was shorter when the lubrication was preheated to the same temperature as that of the coolant. Abstract: Low compression end temperatures, high heat loss, and large resistance torque cause difficulty in starting conventional diesel engines at extremely low temperatures. The diesel-electric hybrid is equipped with high-capacity battery, which can support high-energy-consuming preheating measures to improve low-temperature cold-start performance. However, only a few studies have been conducted on the effect of preheating on the low-temperature cold-start performance of diesel-electric hybrid. In this study, the influence of different preheating temperatures on the performance, emissions, energy consumption, and conversion of a diesel-electric hybrid was experimentally investigated by designing an environmental simulation system and a preheating system. The results showed that intake air preheating consumed less energy and maintained a high energy conversion efficiency. As the intake air temperature increased, the combustion conditions improved, increasing the indicated mean effective pressure and enhancing combustion stability. However, intake preheating was invalid when the ambient temperature was below 244 K because of the high heat loss and large resistance torque. As the coolant temperature increased, the ignition delay period was significantly reduced, allowing the maximum pressure in the cylinder to increase. The corresponding position became closer to the top dead center, resulting in a steady increase in the speed rise rate, a reduction in hydrocarbon emissions from 1403 ppm to 298 ppm, and a reduction in opacity from 85% to 43%. The increase in the lubrication temperature mainly decreased the resistance torque, resulting in a reduction in the drag time and rise time of 0.37 s and 2.21 s, respectively. At 233 K, the minimum energy consumption of the combined preheating of the coolant and intake air was 2557 kJ. In contrast, the combined preheating of the lubricant and intake air was only 379 kJ, but the emission performance of coolant preheating was better than that of lubricant preheating. This result could be considered as the constraint boundary for optimizing the total equivalent energy consumption and is useful for optimizing the preheating strategy and development of diesel-electric-hybrid low-temperature thermal management.